2012
DOI: 10.1103/physreve.85.057204
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude death with mean-field diffusion

Abstract: We study the dynamics of nonlinear oscillators under mean-field diffusive coupling. We observe that this form of coupling leads to amplitude death via a synchronization transition in the parameter space of the coupling strength and mean-field control parameter. A general criterion for amplitude death for any given dynamical system with mean-field diffusion is obtained, and these dynamical transitions are characterized using various indices such as average phase difference, Lyapunov exponents, and average ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…This observation is shown in Fig.2. This is similar as reported in literature [34], [35]. Now with the application of second channel coupling (proper + value) we observe that the trivial steady state of ' state variable becomes unstable and give birth of two new IHSS through symmetry breaking (i.e.…”
Section: Numerical Simulation Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…This observation is shown in Fig.2. This is similar as reported in literature [34], [35]. Now with the application of second channel coupling (proper + value) we observe that the trivial steady state of ' state variable becomes unstable and give birth of two new IHSS through symmetry breaking (i.e.…”
Section: Numerical Simulation Resultssupporting
confidence: 71%
“…But in all cases the coupled system has been under single channel coupling and converges to a common steady state showing AD in them. Sharma et al already reported AD with mean field diffusion in [34], [35]. We explore the dynamics of such MFD coupled Chua's circuit when an additional diffusive coupling has been employed through another channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5]. Mean Field Diffusion [27] which induces AD in identical systems coupled by similar variables. The studies so far showed that AD in such a configuration can occur only under parameter mismatch [15].…”
Section: Scenariosmentioning
confidence: 99%
“…Other schemes such as environmental coupling [26], mean-field diffusion [27], gradient coupling [28], partial time varying delay [29] and indirect coupling [30] for stabilizing AD have also been proposed. In this review, in the next section we discuss these recently proposed scenarios for AD, namely time-varying delays, environmental coupling and other types of interactions.…”
mentioning
confidence: 99%